Time-domain spectroscopy of methane excited by resonant high-energy mid-IR pulses. (12th July 2021) - Crippa, G; Faccialà, D; Prasannan Geetha, P; Pusala, A; Musheghyan, M; Assion, A; Bonanomi, M; Cinquanta, E; Ciriolo, A G; Devetta, M; Fazzi, D; Gatto, L; et al.
Abstract: We describe the implementation of nonlinear time-domain spectroscopy of rotovibrational IR-active modes in methane through broadband Four-Wave Mixing driven by resonant high-energy mid infrared laser pulses. At high driving pulse intensities we observe an efficient vibrational ladder climbing triggered in the molecules. This study opens the possibility to impulsively and selectively excite molecules of biological interest to high-lying vibrational states and to characterize their dynamics.